Ratite phylogeny and distribution with comments on evolutionary processes - Coldiron, Ronn William (Open Science Journal, 2023)
ABSTRACT This paper explains the ubiquitous nature of character conflicts in a taxonomic group, and the ratites are a typical example. Convergence due to similar selection pressures is usually invoked to explain these contradictions. Two alternate mechanisms, orthogenesis and genetic drift, are proposed to explain contradictory distributions of derived characters. It begins with the premise that natural selection and organic change which follows can only occur once a genetic trait is expressed in a phenotype whereas either genetic drift or orthogenesis allows genetic change to proceed regardless of phenotypic expression. Genetic drift or orthogenesis when coupled with homeostasis point to alternate explanations of geographic distribution, a much older age of origin for taxonomic groups, and the explosion of diversity which occurs after major extinction events as well as at the beginning of the Cambrian. The non-concurrence between ratites' southern hemisphere distribution and the sequence of continental breakup are reconciled when assuming these alternate mechanisms are responsible. Characters currently used to test phyogenetic hypotheses are called into question as well as Occam's razor and assumptions used in Bayesian inference. The disparity between a taxon's first appearance in the fossil record and it's time of origin as determined by genetic clock studies is real and not the result of error. Running Head: RATITE PHYLOGENY AND EVOLUTION